Wide distribution of carbapenem resistant Acinetobacter baumannii in burns patients in Iran - Farshadzadeh, Zahra; Hashemi, Farhad B.; Rahimi, Sara; Pourakbari, Babak; Esmaeili, Davoud; Haghighi, Mohammad A.; Majidpour, Ali; Shojaa, Saeed; Rahmani, Maryam; Gharesi, Samira; Aziemzadeh, Masoud; Bahador, Abbas (Frontiers in Microbiology, 2015)
Antimicrobial resistance in carbapenem non-susceptible Acinetobacter baumannii (CNSAb) is a major public health concern globally. This study determined the antibiotic resistance and molecular epidemiology of CNSAb isolates from a referral burn center in Tehran, Iran. Sixty-nine CNSAb isolates were tested for susceptibility to antimicrobial agents using the E test methodology. Multiple locus variable number tandem repeat analysis (MLVA), Multilocus sequence typing (MLST) and multiplex PCR were performed. PCR assays tested for ambler classes A, B, and D β-lactamases. Detection of ISAba1, characterization of integrons, and biofilm formation were investigated. Fifty-three (77%) isolates revealed XDR phenotypes. High prevalence of blaOXA-23-like (88%) and blaPER-1 (54%) were detected. ISAba1 was detected upstream of blaADC, blaOXA-23-like and blaOXA51-like genes in, 97, 42, and 26% of isolates, respectively. Thirty-one (45%) isolates were assigned to international clone (IC) variants. MLVA identified 56 distinct types with six clusters and 53 singleton genotypes. Forty previously known MLST sequence types forming 5 clonal complexes were identified. The Class 1 integron (class 1 integrons) gene was identified in 84% of the isolates. The most prevalent (33%) cassette combination was aacA4-catB8-aadA1. The IC variants were predominant in the A. baumannii lineage with the ability to form strong biofilms. The XDR-CNSAb from burned patients in Iran is resistant to various antimicrobials, including tigecycline. This study shows wide genetic diversity in CNSAb. Integrating the new Iranian A. baumannii IC variants into the epidemiologic clonal and susceptibility profile databases can help effective global control measures against the XDR-CNSAb pandemic.